MODEL OF COSTUMER SATISFACTION DETERMINANTS: SERVICE QUALITY, PRICE, AND ACCESSIBILITY AS KEY VARIABLES - Muffida, Nur Indah; Djunaidi; Angga Rizka Lidiawan (Jurnal Dinamika Ekonomi Syariah, 2025)
This study aims to determine the Influence of Service Quality, Price and Location on Consumer Satisfaction in Ndalem Gawanda Nganjuk. This study uses a quantitative approach with multiple linear regression analysis methods to test the hypothesis after going through validity, reliability, and classical assumption tests. Data were obtained by distributing questionnaires to 67 respondents using the accidental sampling method. The results showed that Service Quality, Price and Location have a positive and significant effect on Consumer Satisfaction. The better the quality of service provided, the more competitive the price offered, and the more strategic the location of Ndalem Gawanda, the higher the level of consumer satisfaction.